Strategi Manajemen Usaha Bumdes Dalam Pengembangan Produk Olahan Nira Aren di Desa Talaitad Utara - Maryadi, Dominikus Andreo; Pontorondo, Immanuel Christian; Runtuwene, Treesje Lusje; Walangitan, Loula Luzy Lenny; Deisy Lusiana (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the business management strategies implemented by Talaut Jaya Village-Owned Enterprise (BUMDes) in developing palm sap-based products in Talaitad Utara Village, South Minahasa Regency. The research uses a qualitative approach with in-depth interviews conducted with BUMDes management on April 1, 2025. The findings reveal that Talaut Jaya adopts adaptive, locally grounded management strategies across four key aspects: planning, organizing, implementation, and supervision. Planning is carried out through participatory discussions, organizing emphasizes community collaboration, implementation focuses on traditional production methods as a product differentiation strategy, and supervision is conducted through trust-based social monitoring. The study shows that business management strategies in rural areas can develop organically from local practices without relying on formal corporate models. This research offers valuable insights for community-based management approaches in the development of village economies